2004
DOI: 10.1089/tmj.2004.10.s-45
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Pediatric Telehome Care Support Following Hospitalization: A Report on Preference and Satisfaction

Abstract: The delivery of health care is often segmented into sectors. In Canada, hospital care has traditionally been distinct from community care, and thus the transition of patients across sectors has been challenging. This paper focuses on the systematic development of an integrated model of care for children, for the purpose of smoothing the transition from hospital to home. The new service model uses emerging telecommunications technology to link hospital care providers to patients at home and is termed "telehomec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…However, due to the serial nature of the interviews, and the consistency of positive findings and passion of the discourses, we believe that the findings are valid. Furthermore, the findings of this study are consistent with the results of quantitative evaluations of satisfaction with care, and of quality of life from this population, in which a rigorous pre‐post statistical analysis was used (Dick et al . 2004, Young et al.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, due to the serial nature of the interviews, and the consistency of positive findings and passion of the discourses, we believe that the findings are valid. Furthermore, the findings of this study are consistent with the results of quantitative evaluations of satisfaction with care, and of quality of life from this population, in which a rigorous pre‐post statistical analysis was used (Dick et al . 2004, Young et al.…”
Section: Discussionsupporting
confidence: 86%
“…In the THC study, the entry of medical technology and caregiver roles into the home was less intrusive and disruptive to family function than the prospect of ongoing hospitalisation, and provided additional security for these families. The overall findings of this study also offer an explanation for the strong preferences families reported for THC and their high levels of satisfaction with the service (mean satisfaction score of 82.8), previously reported by this group (Dick et al . 2004).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the realities of some contexts can make this ideal impracticable, eight examples of researchers using phased approaches (featuring multiple related studies) to development and evaluation of their interventions were found here [8,10,18,21,25,30,65,66,77,78,92-94,102-105,108,109]. …”
Section: Discussionmentioning
confidence: 99%
“…** Both studies in which PCIs were evaluated (1 prepost study that was focused on children with multisystem complex illnesses and 1 prospective cohort study that was focused on the general population of children hospitalized) revealed an association with improved satisfaction. 43,86 CCIs were also associated with improved satisfaction across patient populations, including effective studies in children with chronic illnesses (n = 7), 43,44,48,49,52,53,64 patients in the NICU (n = 2), 78,80 and the general hospitalized population (n = 4). 86,87,89,94 CCIs that were associated with improved satisfaction included assistance with scheduling follow-up care, 43,53,89 in-home visits or follow-up telephone calls, 44,48,49,53,64,86,94 and intensive discharge planning.…”
Section: Results Of Individual Studies Regarding Patient And/or Caregmentioning
confidence: 99%